Pengawasan dan Pengendalian Peredaran Minuman Beralkohol di Desa Paya Gambar Kecamatan Batang Kuis Kabupaten Deli Serdang - Sayyidina, Sayyidina; Nababan, Ramsul (SAKOLA: Journal of Sains Cooperative Learning and Law, 2025)
This study aims to determine the implementation of Supervision and Control of the Distribution of Alcoholic Beverages as an indication to determine the inhibiting factors for supervision and control of the distribution of alcoholic beverages in Paya Gambar Village, Batang Kuis District, Deli Serdang Regency. This study is a qualitative study, namely a phenomenon of community life experienced by research subjects that human behavior is greatly influenced by the situation of the place so that they are directly involved in the situation of events that occur. Therefore, the researcher uses a qualitative research method because this study will examine and examine how the implementation of supervision and control of the distribution of alcoholic beverages in Paya Gambar Village, Batang Kuis District, Deli Serdang Regency. This study was conducted using interview and observation methods with informants, namely the Village Head, Village Secretary, Village Community. Then the data analysis technique in this study is data reduction, data presentation and drawing conclusions. The results of the study show that, protection against the law of supervision and control of the circulation of alcoholic beverages is obtained after being carried out directly. There are palm wine shops or stalls selling palm wine that do not have a permit for the sales carried out. The government in this case, the form of supervision and control of the circulation of alcoholic beverages is by conducting counseling and socialization related to the negative impacts of consuming alcoholic beverages, and the procedures for managing business permits for the sale of alcoholic beverages. However, the people of Paya Gambar Village are reluctant to get involved, making it difficult for alcoholic beverages to get legal protection. For this reason, socialization and education programs should be carried out routinely by involving community organizations in each region.